Different regimes of the uniaxial elongation of electrically charged viscoelastic jets due to dissipative air drag. (October 2015) - Lauricella, Marco; Pontrelli, Giuseppe; Coluzza, Ivan; Pisignano, Dario; Succi, Sauro
Abstract : Highlights: We examine the role of air drag force in the electrospinning process. We develop a simple stochastic analytical model to investigate the concurrent effects. We analyze the dynamics of nanofibers under stochastic perturbation in the early stage of the electrospinning process. Abstract: We investigate the effects of dissipative air drag on the dynamics of electrified jets in the initial stage of the electrospinning process. The main idea is to use a Brownian noise to model air drag effects on the uniaxial elongation of the jets. The developed numerical model is used to probe the dynamics of electrified polymer jets at different conditions of air drag force, showing that the dynamics of the charged jet is strongly biased by the presence of air drag forces. This study provides prospective beneficial implications for improving forthcoming electrospinning experiments.